Indicators of the Structure of the UAE Economy and their Effects on the Economic Strength for the Period (2010-2020): A Study in Geopolitics - Muhaimeed al-Jubouri, khatab Saad (Journal of Tikrit University for Humanities, 2024)
Economic indicators are of great importance in knowing the size of the state’s economic power, as there is a direct relationship between economic resources and the state’s political and strategic weight and the role of economic resources in terms of their quality and quantity and how they are harnessed to build the state’s economy. The diversity and growth of the state’s economic sectors is one of the most important indicators of strength, through which the size of the economic strength can be known, as the UAE is one of the countries that seeks to develop its economic structure based on geographical foundations and available resources to enhance its national security and gain a comparative advantage for its economy in light of its connection to the global economic system. Geographical bases are among the basic elements in knowing the extent of the country’s economic strength and its regional and international standing as a result of the economic advantages it provides to the country. In this regard, the natural, human, and economic foundations of the emirates will be addressed. Population foundations are the basis for knowing the economic strength of the state, as the population has a significant impact on the political weight of the state, and the size of the population alone was not the decisive factor in determining the strength of the state.